Process for preparing c2-C4 hydrocarbons and formulated mixed catalysts
By preparing the prepared mixed catalyst, combining the metal oxide catalyst and the microporous catalyst, and bonding through the binder, the problems of low carbon conversion and poor catalyst stability in the prior art are solved, and the effect of efficient conversion of carbon-containing gases to C2 to C4 hydrocarbons is achieved.
Patent Information
- Application Number
- CN202380052763.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-22
- Filing Date
- 2023-07-21
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, in the process of converting carbon-containing gas into C2 to C4 hydrocarbons, the carbon conversion rate is low and the catalyst stability is poor, resulting in low yield and rapid catalyst deactivation.
A formulated mixed catalyst is prepared, including a combination of metal oxide catalyst components, microporous catalyst components and binder. The mixed catalyst forms a single catalyst body by combining the metal oxide catalyst component with the microporous catalyst component and bonding through a binder to improve conversion and stability.
The efficient conversion of carbon-containing gases to C2 to C4 hydrocarbons is achieved, which improves the carbon conversion rate and the stability of the catalyst and extends the service life of the catalyst.
Smart Images

Figure BDA0005234164180000151 
Figure BDA0005234164180000201
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of U.S. Provisional Patent Application Serial No. 63 / 391,481, filed on July 22, 2022, which is hereby incorporated by reference in its entirety. Technical Field
[0003] The present disclosure relates to methods for efficiently converting various carbonaceous feed streams into C2 to C4 hydrocarbons. In particular, the present disclosure relates to the preparation of formulated mixed catalysts and the use of formulated mixed catalysts to achieve high conversion of carbonaceous gas feeds, thereby producing good carbon conversion and high yields of desired products. Background Art
[0004] For many industrial applications, hydrocarbons are used or used as starting materials to produce plastics, fuels and various downstream chemicals. Such hydrocarbons include C2 to C4 materials such as ethene, propene and butene (also commonly referred to as ethylene, propylene and butylene, respectively). A variety of processes have been developed for the production of these lower hydrocarbons, including petroleum cracking and various synthetic methods.
[0005] Synthetic processes for converting feed carbon into desired products, such as hydrocarbons, are known. Different types of catalysts have been investigated as well as different types of feed streams and ratios of feed stream components.
[0006] Many of these synthesis processes have low carbon conversions, and much of the feed carbon is not converted and leaves the process in the same form as the feed carbon, or is converted to CO2. In addition, these synthesis processes can have low stability over time, and the catalyst quickly loses its activity for carbon conversion to the desired product. Therefore, there is a need for methods and catalytic systems that increase the yield of C2 to C4 hydrocarbons, particularly as run time increases. Summary of the invention
[0007] Embodiments of the present disclosure solve these needs and other needs by the method for preparing the mixed catalyst of preparation and the method for using such catalyst.The mixed catalyst of preparation as described herein comprises the combination of metal oxide catalyst component, microporous catalyst component and binding agent.Use binding agent to merge metal oxide catalyst component and microporous catalyst component into single catalyst body.Then, the mixed catalyst of this preparation can be used for the feed stream containing hydrogen and carbonaceous gas, such as synthesis gas directly converted into C2 to C4 hydrocarbon.Metal oxide catalyst component and microporous catalyst component can be operated in series, so that the mixed catalyst of preparation can directly and selectively convert feed stream containing hydrogen and carbonaceous gas, such as synthesis gas into C2 to C4 hydrocarbon with high olefin / paraffin ratio.
[0008] According to one or more embodiments of the present disclosure, a method for preparing a formed hybrid catalyst may include: mixing a metal oxide catalyst component and a microporous catalyst component, wherein the metal oxide catalyst component comprises gallium oxide and zirconium oxide, wherein the zirconium oxide has a macropore fraction of less than 0.3, and the microporous catalyst component comprises a molecular sieve having an 8-membered ring (MR) pore opening; adding a binder to the metal oxide catalyst component and the microporous catalyst component to form a paste, wherein the binder is a colloidal solution, suspension or gel of a binder precursor comprising an oxide or hydroxide of aluminum, an oxide or hydroxide of zirconium, or a mixture thereof; and extruding the paste to produce the formed hybrid catalyst.
[0009] According to one or more embodiments of the present disclosure, a method for preparing C2 to C4 hydrocarbons may include: introducing a feed stream including hydrogen and a carbon-containing gas into a reaction zone of a reactor, the carbon-containing gas being selected from the group consisting of carbon monoxide, carbon dioxide, and a mixture thereof; and converting the feed stream into a product stream including C2 to C4 hydrocarbons in the reaction zone in the presence of a formed mixed catalyst, wherein the formed mixed catalyst may include: a metal oxide catalyst component, the metal oxide catalyst component comprising gallium oxide and zirconium oxide, wherein the zirconium oxide has a macropore fraction of less than 0.3; a microporous catalyst component, the microporous catalyst component being a microporous catalyst component of a molecular sieve having an 8-membered ring (MR) pore opening; and a binder, the binder comprising alumina, zirconium oxide, or a mixture thereof.
[0010] Additional features and advantages will be set forth in the following Detailed Description, and in part will become apparent to those skilled in the art from that Description or may be learned by practicing the embodiments described herein, including the following Detailed Description in addition to the claims.
[0011] It is to be understood that both the foregoing general description and the following detailed description describe various embodiments, and are intended to provide an overview or framework for understanding the nature and character of the claimed subject matter. DETAILED DESCRIPTION
[0012] Reference will now be made in detail to embodiments of methods for preparing a formulated mixed catalyst and for forming C2 to C4 hydrocarbons from a feed stream comprising hydrogen and a carbonaceous gas. As used herein, "carbonaceous gas" refers to a gas selected from carbon monoxide, carbon dioxide, and mixtures thereof. As used herein, "synthesis gas" refers to a gas comprising hydrogen and a carbonaceous gas. In one or more embodiments, the method for preparing a formulated mixed catalyst may include mixing a metal oxide catalyst component and a microporous catalyst component to form a mixture, adding a binder to the mixture of the metal oxide catalyst component and the microporous catalyst component to form a paste, and extruding the paste to produce a formulated mixed catalyst, followed by drying and calcining. The metal oxide catalyst component may include gallium oxide and zirconium oxide, wherein the zirconium oxide may have a macropore fraction of less than 0.30. The microporous catalyst component may include a molecular sieve having an 8-membered ring (MR) pore opening. The binder may be a colloidal solution, suspension, or gel of a binder precursor comprising an oxide or hydroxide of aluminum, an oxide or hydroxide of zirconium, or a mixture thereof.
[0013] In one or more embodiments, a method for preparing C2 to C4 hydrocarbons may include introducing a feed stream comprising hydrogen and a carbon-containing gas selected from the group consisting of carbon monoxide, carbon dioxide, and mixtures thereof into a reaction zone of a reactor; and converting the feed stream into a product stream comprising C2 to C4 hydrocarbons in the reaction zone in the presence of a formulated mixed catalyst. The formulated mixed catalyst may be formed by a method for preparing a formulated mixed catalyst as described herein.
[0014] The use of the mixed catalyst of this preparation is known in the field of hydrocarbon products such as diesel or aromatic compounds. However, many known mixed catalysts of preparation are inefficient for forming C2 to C4 hydrocarbons (for C2-C4 paraffins and for C2 to C4 olefins) by the feed stream comprising hydrogen and carbonaceous gas, because they show low feed carbon conversion, and / or deactivate quickly in use. In contrast, when compared with a mixed catalyst comprising a zirconium oxide with a relatively high macropore fraction (indicating a higher fraction of larger pores) with a metal oxide catalyst component, even if the catalyst run time increases, the mixed catalyst of the preparation disclosed and described herein also shows high and stable C2 to C4 hydrocarbon yields. The preparation and composition of the mixed catalyst of this type of preparation used in an embodiment are discussed below.
[0015] In one or more embodiments, the term "metal oxide catalyst component" may refer to a metal oxide catalyst support material coated with one or more dopants, for example, the metal oxide catalyst component may include a zirconium oxide support material coated with one or more dopants including gallium oxide and rare earth oxides. In one or more embodiments, the term "microporous catalyst component" may refer to a catalyst component comprising [SiO4] and [AlO4] - A molecular sieve zeolite component of a crystalline aluminosilicate having a three-dimensional interconnected network of tetrahedra. In one or more embodiments, the term "microporous catalyst component" may refer to a catalyst component comprising a catalyst having [PO4] + and [AlO4] - A molecular sieve zeolite component of a crystalline silicoaluminophosphate of a three-dimensional interconnected network of tetrahedra, in which aluminum and / or phosphorus are partially substituted by silicon. In one or more embodiments, the term "binder" may refer to a material capable of binding a metal oxide catalyst component to a microporous catalyst component to combine these components into a single catalyst body.
[0016] In one or more embodiments, the metal oxide catalyst component may include zirconium oxide, wherein the zirconium oxide serves as a metal oxide carrier. The term "metal oxide carrier" may refer to a carrier material of other components (such as gallium oxide and rare earth oxide) of the metal oxide catalyst component. In some embodiments, the zirconium oxide of the metal oxide catalyst component may include micropores. The term "micropore" may refer to a pore of a material in which the diameter of one or more pores is less than 2nm. In some embodiments, the zirconium oxide of the metal oxide catalyst component may include mesopores. The term "mesopore" may refer to a pore of a material in which the diameter of one or more pores is 2nm-50nm. In some embodiments, the zirconium oxide of the metal oxide catalyst component may include macropores. The term "macropore" may refer to a pore of a material in which the diameter of one or more pores is greater than or equal to 80nm. It has been found herein that a large number of macropores in zirconium oxide increase the deactivation of the mixed catalyst. Therefore, it is desirable to have a small amount of macropores in zirconium oxide.
[0017] The term "macropore fraction" may refer to the ratio of the macropore volume of the zirconia support to the total pore volume of pores of the zirconia support having a size less than 500 nm. To test the macropore fraction, a mercury intrusion test may be used, in which the porosity of the zirconia is measured by immersing the material in mercury and applying a controlled pressure to the system so that the mercury can penetrate into the pores of the material. Based on the pressure required to force the mercury into certain pores of the zirconia support, the pore size and pore volume may be calculated. Correlating the pore size with the associated pressure may be achieved using the following formula I, where D is the diameter of the zirconia support pores, P is the pressure required for mercury to penetrate the zirconia support pores, γ is the surface tension of mercury, and θ is the contact angle between zirconia and mercury:
[0018] (Formula I)
[0019] For example, when the NorPro SZ31164 zirconia support was tested using mercury intrusion, the total intrusion volume of mercury into the macropores (i.e., pores with diameters of 80 nm to 500 nm) of the zirconia support was found to be 0.0406 mL / g, and the total intrusion volume of mercury into all pores with diameters ranging from 3 nm to 500 nm was 0.294 mL / g, thus yielding a macropore fraction of 0.138. Without being bound by theory, it is believed that the lower macropore fraction of the zirconia support enables the formulated hybrid catalyst to achieve higher compound conversions and have lower deactivation rates in a feed stream comprising hydrogen and a carbon-containing gas.
[0020] In an embodiment, the metal oxide catalyst component comprises gallium oxide. As used herein, "gallium oxide" refers to gallium in various oxidation states. In an embodiment, gallium oxide may be deposited on the surface of zirconium oxide or form a solid solution with zirconium oxide. In other embodiments, gallium oxide may include, but is not limited to, Ga2O3, GaO(OH), and Ga5O7(OH). Gallium oxide may also include polymorphs of Ga2O3, such as monoclinic (β-Ga2O3), rhombohedral (α-Ga2O3), defective spinel (γ-Ga2O3), cubic (δ-Ga2O3), or orthorhombic (ε-Ga2O3) structures. In other embodiments, gallium oxide may include gallium in more than one oxidation state. For example, individual gallium may be in different oxidation states. Gallium oxide is not limited to gallium comprising a uniform oxidation state.
[0021] In short, the mixed catalyst of preparation is closely coupled to the independent reaction on each independent catalyst in two independent catalysts.In the first step, the feed stream of the carbonaceous gas of the group consisting of hydrogen (H2) and the mixture of carbon monoxide (CO), carbon dioxide (CO2) or CO and CO2, such as synthesis gas, is converted into intermediates, such as oxygenated hydrocarbons.In the subsequent step, these intermediates are converted into the product stream comprising hydrocarbons (mainly short-chain hydrocarbons, such as C2 to C4 hydrocarbons).The continuous formation and consumption of the intermediate oxygenated compound formed by the reaction of the second step in the first step ensure that there is no thermodynamic limitation to conversion.
[0022] In one or more embodiments, the prepared mixed catalyst has a particle size of 0.5 mm to 6.0 mm. For example, the prepared mixed catalyst can have a particle size of at least 0.5 mm, at least 1.0 mm, at least 1.5 mm, at least 2.0 mm, at least 2.5 mm, at least 3.0 mm, at least 3.5 mm, at least 4.0 mm, at least 4.5 mm, at least 5.0 mm, at least 5.5 mm, or even 6.0 mm. In embodiments, the prepared mixed catalyst can have a particle size of less than 3.0 mm, such as less than 2.5 mm, less than 2.0 mm, less than 1.5 mm, less than 1.0 mm, or less than 0.5 mm. In embodiments, the prepared mixed catalyst may have a particle size of 0.5 mm to 5.5 mm, 0.5 mm to 5.0 mm, 0.5 mm to 4.5 mm, 0.5 mm to 4.0 mm, 0.5 mm to 3.5 mm, 0.5 mm to 3.0 mm, 0.5 mm to 2.5 mm, 0.5 mm to 2.0 mm, or 0.5 mm to 1.5 mm. In embodiments, the prepared mixed catalyst may have a particle size in the range of 1.0 mm to 6.0 mm, 1.5 mm to 6.0 mm, 2.0 mm to 6.0 mm, 2.5 mm to 6.0 mm, 3.0 mm to 6.0 mm, 3.5 mm to 6.0 mm, 4.0 mm to 6.0 mm, 4.5 mm to 6.0 mm, 5.0 mm to 6.0 mm, or 5.5 mm to 6.0 mm. The particle size may be substantially the shortest dimension of the catalyst particles. For example, when the prepared mixed catalyst has a hollow cylinder or annular shape, the particle size is the thickness of the hollow cylinder wall. When the prepared mixed catalyst has a spherical shape, the particle size is the diameter of the sphere. The particle size of the prepared mixed catalyst can be controlled by selecting the extrusion die diameter and measured by the dynamic image analysis method.
[0023] In one or more embodiments, the zirconium oxide of the metal oxide catalyst component may have a macropore fraction of less than 0.30, such as having a macropore fraction of less than 0.25, less than 0.20, less than 0.15, or even less than 0.10. In one or more embodiments, the macropore fraction may be from 0.05 to 0.25, 0.10 to 0.25, or 0.10 to 0.20. In embodiments, the macropore fraction may be from 0.05 to 0.25, 0.05 to 0.20, 0.05 to 0.15, or 0.0 to 0.10. In embodiments, the macropore fraction may be from 0.10 to 0.30, 0.15 to 0.30, 0.20 to 0.30, or 0.25 to 0.30.
[0024] The metal oxide catalyst component may include gallium oxide and / or zirconium oxide (ZrO2). As used herein, the zirconium oxide used in the embodiments disclosed and described herein in the metal oxide catalyst component of the formulated mixed catalyst may be a "phase pure zirconium oxide", which is defined herein as a zirconium oxide to which no other materials are intentionally added during formation. Therefore, "phase pure zirconium oxide" includes zirconium oxide with a small amount of components other than zirconium (including oxides other than zirconium oxide) that are unintentionally present in the zirconium oxide as a natural part of the zirconium oxide formation process, such as hafnium (Hf). Therefore, unless otherwise specifically stated, "zirconia" and "phase pure zirconium oxide" as used herein may be used interchangeably. In other embodiments, the zirconium oxide may be a non-phase pure zirconium oxide, such as zirconium oxide doped with calcium, yttrium oxide, lanthanum, cerium or a rare earth element.
[0025] In one or more embodiments, the composition of the metal oxide catalyst component is expressed by the weight percent of gallium relative to pure zirconium oxide (considering the stoichiometry of ZrO2 and Ga2O3). In one or more embodiments, the composition of the metal oxide catalyst component is expressed by the weight percent of gallium. For example, the metal oxide catalyst component can contain 0.1 wt % to 10 wt % gallium, such as 0.1 wt % to 9 wt %, 0.1 wt % to 8 wt %, 0.1 wt % to 7 wt %, 0.1 wt % to 6 wt %, 0.1 wt % to 5 wt %, 0.1 wt % to 4 wt %, 0.1 wt % to 3 wt %, 0.1 wt % to 2 wt %, 0.5 wt % to 10 wt %, 1 wt % to 10 wt %, 2 wt % to 10 wt %, 3 wt % to 10 wt %, 4 wt % to 10 wt %, 5 wt % to 10 wt %, 6 wt % to 10 wt %, 7 wt % to 10 wt %, 8 wt % to 10 wt %, 9 wt % to 10 wt %, 1 wt % to 5 wt %, 3 wt % to 10 wt %, 3 wt % to 7 wt % gallium.
[0026] In embodiments, the metal oxide catalyst component may comprise lanthanum oxide. In other embodiments, additional elements from the group of rare earth elements, lanthanides and / or transition metals (such as Ni, Pd or Pt) are co-deposited with the gallium precursor or introduced only when a mixed composition comprising gallium oxide and zirconium oxide has first been prepared.
[0027] In the embodiments disclosed herein, the composition of the metal oxide catalyst component can be represented by the weight percentage of lanthanum oxide metal relative to pure zirconium oxide (considering ZrO2 stoichiometry). In one or more embodiments, the composition of the metal oxide catalyst component can be represented by the weight percentage of lanthanide based on oxide. According to one or more embodiments, the metal oxide catalyst component may contain 0.1 wt% to 7 wt% lanthanide, such as 0.5 wt% to 7 wt%, 1 wt% to 7 wt%, 2 wt% to 7 wt%, 3 wt% to 7 wt%, 4 wt% to 7 wt%, 5 wt% to 7 wt%, 6 wt% to 7 wt%, 0.1 wt% to 6 wt%, 0.1 wt% to 5 wt%, 0.1 wt% to 4 wt%, 0.1 wt% to 3 wt%, 0.1 wt% to 2 wt%, 0.1 wt% to 1 wt%, 0.5 wt% to 5 wt%, 0.5 wt% to 3 wt%, 3 wt% to 7 wt%, or 5 wt% to 7 wt% lanthanide.
[0028] In an embodiment, one method of preparing the metal oxide catalyst component of the mixed catalyst is by incipient wetness impregnation. In this method, an aqueous mixture of a gallium precursor material (such as gallium (III) nitrate hydrate (Ga (NO3) 3·xH2O)) and / or an aqueous mixture of a rare earth metal precursor material (such as lanthanum (III) nitrate hexahydrate (La (NO3) 3·6H2O)) is added to a zirconium oxide powder. In an embodiment, the aqueous mixture containing the gallium precursor material and / or the rare earth metal precursor material can be sprayed, added dropwise, or any other similar method so that the aqueous mixture is uniformly or nearly uniformly distributed on the zirconium oxide. This can be achieved by mixing the zirconium oxide powder and the aqueous mixture. In other embodiments, gallium oxide and / or rare earth oxides can be deposited or distributed on the zirconium oxide oxide by a chemical vapor deposition (CVD) method. However, the method for preparing the metal oxide catalyst component of the mixed catalyst is not particularly limited, and any method that can apply fine layers of gallium oxide and rare earth oxide to the surface of zirconium oxide can be used according to the embodiment. It will be appreciated that the total amount of gallium precursor and rare earth metal precursor mixed with the zirconium oxide will be determined based on the desired target amounts of gallium and rare earth metal in the metal oxide catalyst component.
[0029] According to an embodiment, the zirconium oxide particles may include zirconium oxide particles having a crystalline structure. In an embodiment, the zirconium oxide particles may include zirconium oxide particles having a monoclinic structure. In one or more embodiments, the zirconium oxide particles consist essentially of or consist of crystalline zirconium oxide particles, and in an embodiment, the zirconium oxide particles consist essentially of or consist of monoclinic zirconium oxide particles.
[0030] In an embodiment, the surface area of the zirconium oxide particles may be greater than or equal to 5 square meters per gram (m 2 For example, the surface area of the zirconium oxide particles may be at least 5 m 2 / g, at least 10m 2 / g, at least 20m 2 / g, at least 50m 2 / g, at least 75m 2 / g, at least 100m 2 / g, at least 125m 2 / g or at least 150m 2 / g. In an embodiment, the surface area of the zirconium oxide particles may be 5m 2 / g to 200m 2 / g, 10m 2 / g to 200m 2 / g, 20m 2 / g to 200m 2 / g, such as 30m 2 / g to 200m 2 / g, 40m 2 / g to 200m 2 / g, 50m 2 / g to 200m 2 / g, 60m 2 / g to 200m 2 / g, 70m 2 / g to 200m 2 / g, 80m 2 / g to 200m 2 / g, 90m 2 / g to 200m 2 / g、100m 2 / g to 200m 2 / g, 110m 2 / g to 200m 2 / g, 120m 2 / g to 200m 2 / g, 130m 2 / g to 200m 2 / g or 140m 2 / g to 200m 2 / g. In an embodiment, the surface area of the zirconium oxide particles may be 5m 2 / g to 180m 2 / g, 5m 2 / g to 160m 2 / g, 5m 2 / g to 140m 2 / g, 5m 2 / g to 120m2 / g, 5m 2 / g to 100m 2 / g, 5m 2 / g to 90m 2 / g, 5m 2 / g to 80m 2 / g, 5m 2 / g to 70m 2 / g, 5m 2 / g to 60m 2 / g, 5m 2 / g to 50m 2 / g, 5m 2 / g to 40m 2 / g, 5m 2 / g to 30m 2 / g, 5m 2 / g to 20m 2 / g or 5m 2 / g to 10m 2 / g. In an embodiment, the surface area of the zirconium oxide particles may be 10m 2 / g to 160m 2 / g, 20m 2 / g to 130m 2 / g, 30m 2 / g to 120m 2 / g, 40m 2 / g to 110m 2 / g, 50m 2 / g to 100m 2 / g, 60m 2 / g to 90m 2 / g or 70m 2 / g to 80m 2 / g.
[0031] Once the gallium precursor and zirconium oxide particles are thoroughly mixed, the metal oxide catalyst component can be dried at a temperature below 200 degrees Celsius (° C.), such as below 175° C., below 150° C., below 100° C., or about 85° C. In embodiments, the metal oxide catalyst component can be dried at a temperature of 40° C. to 200° C. In embodiments, the metal oxide catalyst component can be dried at a temperature of 40° C. to 160° C., 40° C. to 120° C., or 40° C. to 80° C. In embodiments, the metal oxide catalyst component can be dried at a temperature of 80° C. to 200° C., 120° C. to 200° C., or 160° C. to 200° C. After drying, the metal oxide catalyst component can be calcined at a temperature of 400° C. to 800° C., such as 425° C. to 775° C., 450° C. to 750° C., 475° C. to 725° C., 500° C. to 700° C., 525° C. to 675° C., 550° C. to 650° C., 575° C. to 625° C., about 550° C., or about 600° C. After calcination, the composition of the metal oxide catalyst component is determined and reported as the weight percent of gallium relative to the oxide composition of the material.
[0032] It should be understood that, according to embodiments, the metal oxide catalyst component can be prepared by other methods that ultimately produce an intimate contact between the gallium precursor and the zirconium oxide. Some non-limiting examples include vapor deposition of a Ga-containing precursor (organic or inorganic in nature) followed by controlled decomposition thereof. Similarly, the method for dispersing liquid gallium metal can be modified by those skilled in the art to produce an intimate contact between the gallium precursor and the zirconium oxide.
[0033] In one or more embodiments, after the metal oxide catalyst component has been prepared, for example, by the method disclosed above, the metal oxide catalyst component can be mixed with a microporous catalyst component and a binder to form a single catalyst. In an embodiment, the microporous catalyst component can be selected from a molecular sieve having an 8-ring (MR) pore opening and having a framework type selected from the group consisting of the following framework types: CHA, AEI, AFX, ERI, LEV, LTA, UFI, RTH, EDI, GIS, MER, RHO and their combinations, which framework types correspond to the naming conventions of the International Zeolite Association (International Zeolite Association). It should be understood that in an embodiment, both aluminosilicate and silicoaluminophosphate frameworks can be used. Embodiments may include tetrahedral aluminosilicates, ALPO (e.g., tetrahedral aluminophosphates), SAPO (e.g., tetrahedral silicoaluminophosphates) and only silica-based framework silicates. In certain embodiments, the microporous catalyst component can be a silicoaluminophosphate with a chabazite (CHA) framework type. Examples of these may include, but are not necessarily limited to: CHA embodiments selected from SAPO-34 and SSZ-13; and AEI embodiments, such as SAPO-18 and SSZ-39. Combinations of microporous catalyst components having any of the above framework types may also be employed. It should be understood that, depending on the desired product, the microporous catalyst component may have different ring pore openings. For example, depending on the desired product, a microporous catalyst component having an 8-MR to 12-MR pore opening may be used. However, in order to produce C2 to C4 hydrocarbons, a microporous catalyst component having an 8-MR pore opening is used in an embodiment.
[0034] The metal oxide catalyst component and the microporous catalyst component of the mixed catalyst of preparation can be mixed together by any suitable means to realize the uniform mixing of all components before extrusion. The metal oxide catalyst component and the microporous catalyst component can be mixed in powder form initially, to realize uniformity in a suitable dry mixer, such as a ribbon or plow mixer. The binder precursor can be added to the mixture of the metal oxide catalyst component and the microporous catalyst component, and mixed in a suitable heavy industrial mixer capable of handling thick paste preparations. Alternatively, the premixed metal oxide catalyst component and the microporous catalyst component of the dry can be directly fed into the feed screw of a screw extruder together with the binder precursor composition of peptization, and directly mixed in the screw extruder. The mixed catalyst of preparation can be extruded into a desired shape by any suitable extrusion method. The example of shape includes spherical, subspherical, cylindrical, etc. In an embodiment, the metal oxide catalyst component may comprise from 1.0 wt % to 85.0 wt %, such as from 5.0 wt % to 85.0 wt %, from 10.0 wt % to 85.0 wt %, from 15.0 wt % to 85.0 wt %, from 20.0 wt % to 85.0 wt %, from 25.0 wt % to 85.0 wt %, from 30.0 wt % to 85.0 wt %, from 35.0 wt % to 85.0 wt %, from 40.0 wt % to 85.0 wt %, from 45.0 wt % to 85.0 wt %, from 50.0 wt % to 85.0 wt %, from 55.0 wt % to 85.0 wt %, from 60.0 wt % to 85.0 wt %, from 65.0 wt % to 85.0 wt %, from 70.0 wt % to 85.0 wt %, or from 75.0 wt % to 85.0 wt %. In embodiments, the metal oxide catalyst component comprises from 1.0 wt% to 85.0 wt%, from 1.0 wt% to 75.0 wt%, from 1.0 wt% to 70.0 wt%, from 1.0 wt% to 65.0 wt%, from 1.0 wt% to 60.0 wt%, from 1.0 wt% to 55.0 wt%, from 1.0 wt% to 50.0 wt%, from 1.0 wt% to 45.0 wt%, from 1.0 wt% to 40.0 wt%, from 1.0 wt% to 35.0 wt%, from 1.0 wt% to 30.0 wt%, from 1.0 wt% to 25.0 wt%, from 1.0 wt% to 20.0 wt%, from 1.0 wt% to 15.0 wt%, from 1.0 wt% to 10.0 wt%, or from 1.0 wt% to 5.0 wt%.In embodiments, the metal oxide catalyst component accounts for 5.0% to 85.0% by weight of the mixed catalyst formulated, such as 10.0% to 80.0% by weight, 15.0% to 80.0% by weight, 20.0% to 80.0% by weight, 25.0% to 75.0% by weight, 30.0% to 70.0% by weight, 35.0% to 65.0% by weight, 40.0% to 60.0% by weight, or 45.0% to 55.0% by weight. In embodiments, the metal oxide catalyst component accounts for 40.0% to 80.0% by weight of the mixed catalyst formulated, such as 50.0% to 75.0% by weight, 50.0% to 70.0% by weight, 60.0% to 80.0% by weight, 60.0% to 75.0% by weight, or 60.0% to 70.0% by weight.
[0035] The metal oxide catalyst component and the microporous catalyst component can be combined in any mass ratio from 1:10 to 10:1, such as a mass ratio of the metal oxide catalyst component to the microporous catalyst component of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 and 1:10, and a mass ratio of the microporous catalyst component to the metal oxide component of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 and 1:10.
[0036] After the metal oxide catalyst component has been prepared and mixed with the microporous catalyst component, a binder may be added to produce a paste. The binder may be able to hold the metal oxide catalyst component and the microporous catalyst component together. The paste may be extruded to produce a formulated mixed catalyst. The formulated mixed catalyst may be formed by any suitable extrusion method.
[0037] Various binders are considered suitable. For example, the binder may include alumina, zirconium oxide, or both. In embodiments, the binder may include pure alumina. In embodiments, the binder may include pure zirconium oxide. When the binder includes alumina, the alumina binder may be hydrated alumina. The hydrated alumina composition may be prepared from a boehmite precursor with water and a peptizing agent. The binder may be mixed with a metal oxide catalyst component and a microporous catalyst component. After the binder is mixed with the metal oxide catalyst component and the microporous catalyst component, the mixture may be extruded, dried, and / or calcined. After calcination, the binder may form alumina and bind the metal oxide catalyst component and the microporous catalyst component together to provide the mechanical strength of the mixed catalyst prepared by extrusion. Without being bound by any particular theory, other commonly used binders, such as SiO2 and TiO2 may cause a significant loss of catalyst activity poisoning or olefin selectivity. It is not easy to mix two catalyst components into a single catalyst body. A physical mixture of a separately formed metal oxide catalyst component and a separately formed microporous catalyst component (i.e., not forming a single catalyst body) can also reduce the pressure drop on the reactor, but catalytic performance (such as hydrocarbon or olefin selectivity and carbon conversion) may be significantly reduced. A binder comprising alumina, zirconium oxide, or both can mix the metal oxide catalyst component and the microporous catalyst component into a single catalyst body to improve C2 to C4 olefin yield and carbon conversion. Separately forming both the metal oxide catalyst and the microporous catalyst and combining them into a physical mixture does not achieve C2 to C4 carbon conversions, which are obtained using a mixed catalyst formulated as disclosed and described herein.
[0038] In embodiments, the binder may be a colloidal solution, suspension or gel of a binder precursor. The binder precursor may include an oxide or hydroxide of aluminum, an oxide or hydroxide of zirconium, or a mixture thereof. In one embodiment, the binder precursor may include pure alumina, (pseudo) boehmite or gibbsite, or a mixture thereof. In other embodiments, the binder precursor may include pure zirconium oxide, hydrated zirconium oxide, or a mixture thereof. In embodiments where the binder includes hydrated alumina (e.g., pseudo boehmite or gibbsite), an acid is typically added as a peptizing agent. The peptization ratio is defined as the ratio of the number of moles of acid added during peptization to the number of moles of aluminum ([H + ] / [Al]). In one or more embodiments, the peptization ratio may have a [H] of 0.005 to 0.1, 0.01 to 0.1, or about 0.05. + ] / [Al] ratio.
[0039] In an embodiment, the binder may have a 25 m 2 / g to 400m 2 , 50m / g 2 / g to 400m2 / g, 75m 2 / g to 400m 2 , 100m / g 2 / g to 400m 2 , 125m / g 2 / g to 400m 2 , 150m / g 2 / g to 400m 2 , 100m / g 2 / g to 200m 2 , 125m / g 2 / g to 200m 2 , 150m / g 2 / g to 200m 2 , 25m / g 2 / g to 175m 2 , 25m / g 2 / g to 150m 2 , 25m / g 2 / g to 125m 2 , 25m / g 2 / g to 100m 2 , 125m / g 2 / g to 175m 2 , 150m / g 2 / g to 175m 2 , 100m / g 2 / g to 150m 2 , 125m / g 2 / g to 150m 2 / g or 100m 2 / g to 125m 2 / g of surface area.
[0040] Without being bound by any particular theory, it has been found that using templated molecular sieves (e.g., uncalcined) for formulation has a positive impact on catalyst performance and structural characteristics, particularly when strongly acidic conditions, such as a peptization ratio greater than 0.05 or greater than 0.025, are used during the formulation procedure of the formulated hybrid catalyst.
[0041] In embodiments, the mixed metal oxide catalyst component and / or binder is substantially free of silicon and phosphorus. The term "substantially free" may refer to a component being less than 0.5 weight percent (wt.%) in the composition. For example, a metal oxide catalyst component and binder that is substantially free of silicon or phosphorus may have less than 0.5 weight percent silicon or phosphorus based on the total weight of the metal oxide catalyst component and binder.
[0042] The formulated mixed catalyst can be used in a process for converting carbon in a carbonaceous feed stream into C2 to C4 hydrocarbons. Such a process will be described in more detail below.
[0043] According to an embodiment, a feed stream is fed into a reaction zone, the feed stream comprising hydrogen (H2) and a carbon-containing gas selected from carbon monoxide (CO), carbon dioxide (CO2) and a combination thereof. In an embodiment, the H2 gas is present in the feed stream in an amount of 10 volume percent (vol.%) to 90 vol.%, based on the total volume of the H2 gas and the gas selected from CO, CO2 and a combination thereof. The feed stream is contacted with a formulated mixed catalyst as disclosed and described herein in the reaction zone. The formulated mixed catalyst includes a metal oxide catalyst component comprising gallium oxide and zirconium oxide; a microporous catalyst component; and a binder.
[0044] Without being bound by theory, it is understood that the activity of the formulated mixed catalyst will be higher for feed streams containing CO as the carbon-containing gas, and the activity of the formulated mixed catalyst will decrease when a larger portion of the carbon-containing gas in the feed stream is CO. However, this is not to say that the formulated mixed catalyst disclosed and described herein cannot be used in a process in which the feed stream includes CO as all or a majority of the carbon-containing gas.
[0045] The feed stream is contacted with the formulated mixed catalyst in a reaction zone under reaction conditions sufficient to form a product stream comprising C2 to C4 hydrocarbons. According to one or more embodiments, the reaction conditions may include a temperature in the reaction zone ranging from 350°C to 480°C, such as 375°C to 450°C, 400°C to 450°C, 350°C to 425°C, 375°C to 425°C, 400°C to 425°C, 350°C to 400°C, or 375°C to 400°C.
[0046] In embodiments, the reaction conditions include a pressure within the reaction zone of at least 1 bar (100 kilopascals (kPa), such as at least 5 bar (500 kPa), at least 10 bar (1,000 kPa), at least 15 bar (1,500 kPa), at least 20 bar (2,000 kPa), at least 25 bar (2,500 kPa), at least 30 bar (3,000 kPa), at least 35 bar (3,500 kPa), at least 40 bar (4,000 kPa), at least 45 bar (4,500 kPa), at least 50 bar (500 kPa), at least 55 bar (600 kPa), at least 50 bar (700 kPa), at least 50 bar (800 kPa), at least 55 bar (900 kPa), at least 50 bar (1000 kPa), at least 50 bar (1100 kPa), at least 50 bar (1200 kPa), at least 50 bar (1300 kPa), at least 50 bar (1500 kPa), at least 50 bar (1600 kPa), at least 50 bar (1700 kPa), at least 50 bar (1800 kPa), at least 50 bar (1900 kPa), at least 50 bar (1900 kPa), at least 50 bar (1 kPa), at least 50 bar (5,000 kPa), at least 55 bar (5,500 kPa), at least 60 bar (6,000 kPa), at least 65 bar (6,500 kPa), at least 70 bar (7,000 kPa), at least 75 bar (7,500 kPa), at least 80 bar (8,000 kPa), at least 85 bar (8,500 kPa), at least 90 bar (9,000 kPa), at least 95 bar (9,500 kPa), or at least 100 bar (10,000 kPa). kPa). In other embodiments, the reaction conditions include a pressure within the reaction zone of 5 bar (500 kPa) to 100 bar (10,000 kPa), such as 10 bar (1,000 kPa) to 95 bar (9,500 kPa), 15 bar (1,500 kPa) to 90 bar (9,000 kPa), 20 bar (2,000 kPa) to 85 bar (8,500 kPa), 25 bar (2,500 kPa) to 80 bar (8,000 kPa), 30 bar (3 ... In some embodiments, the pressure inside the reaction zone is from 20 bar (2,000 kPa) to 60 bar (6,000 kPa).
[0047] According to embodiments, the gas hourly space velocity (GHSV) in the reaction zone is from 500 per hour ( / hr) to 12,000 / hr, such as from 500 / hr to 10,000 / hr, from 1,200 / hr to 12,000 / hr, from 1,500 / hr to 10,000 / hr, from 2,000 / hr to 9,500 / hr, from 2,500 / hr to 9,000 / hr, from 3,000 / hr to 8,500 / hr, from 3,500 / hr to 8,000 / hr, from 4,000 / hr to 7,500 / hr, from 4,500 / hr to 7,000 / hr, from 5,000 / hr to 6,500 / hr, or from 5,500 / hr to 6,000 / hr. In embodiments, the GHSV within the reaction zone is from 1,800 / hour to 3,600 / hour, such as from 2,000 / hour to 3,600 / hour, 2,200 / hour to 3,600 / hour, 2,400 / hour to 3,600 / hour, 2,600 / hour to 3,600 / hour, 2,800 / hour to 3,600 / hour, 3,000 / hour to 3,600 / hour, 3,200 / hour to 3,600 / hour, or 3,400 / hour to 3,600 / hour. In embodiments, the GHSV within the reaction zone is from 1,800 / hour to 3,400 / hour, such as from 1,800 / hour to 3,200 / hour, from 1,800 / hour to 3,000 / hour, from 1,800 / hour to 2,800 / hour, from 1,800 / hour to 2,600 / hour, from 1,800 / hour to 2,400 / hour, from 1,800 / hour to 2,200 / hour, or from 1,800 / hour to 2,000 / hour. In embodiments, the GHSV within the reaction is from 2,000 / hour to 3,400 / hour, such as from 2,200 / hour to 3,200 / hour, from 2,400 / hour to 3,000 / hour, or from 2,600 / hour to 2,800 / hour.
[0048] In embodiments, when using the formulated mixed catalyst disclosed and described herein and the process conditions disclosed and described herein, carbon conversion can be increased. Within the disclosed process, the conversion of a feed containing carbon oxides and hydrogen can be carried out in a series of reactors, wherein water byproducts are separated (knock-out) by intermediate separation, such as phase separation, membrane separation, or some type of water selective absorption or adsorption method. Without being bound by theory, further continuously directing the partially converted and anhydrous effluent to subsequent reactors and repeating this technical mode of operation will have an overall effect of increasing hydrocarbon yields.
[0049] In embodiments, when using the formulated mixed catalyst disclosed and described herein and the process conditions disclosed and described herein, the process can have a C2-C4 olefin selectivity / paraffin selectivity ratio of greater than or equal to 2, such as having a C2-C4 olefin selectivity / paraffin selectivity ratio of greater than or equal to 2, greater than or equal to 3, greater than or equal to 4, greater than or equal to 5, greater than or equal to 10, greater than or equal to 15, or even a C2-C4 olefin selectivity / paraffin selectivity ratio of 20.
[0050] Example
[0051] The following examples illustrate features of the present disclosure, but are not intended to limit the scope of the present disclosure. For each of the following examples and comparative examples, a microporous catalyst component was prepared as follows: SAPO-34 was synthesized according to a literature procedure (Lok, BM; Messina, CA; Patton, RL; Gajek, RT; Cannan, TR; Flanigen, EM Crystalline silicoaluminophosphates. U.S. Pat. No. 4,440,871A, 1984). When calcined SAPO-34 was used, the material was calcined in air using the following procedure: from 25°C to 600°C at a heating rate of 5°C / min, maintained at 600°C for 4 hours (h), and cooled to 25°C within 4h. The material was sieved into a fraction of less than 200 mesh (less than 75 μm).
[0052] Mercury (Hg) Intrusion Porosimetry on Different ZrO2 Supports
[0053] Mercury (Hg) intrusion analysis was performed on a Micromeritics Autopore IV 9520. Prior to mercury analysis, samples were mechanically degassed under vacuum to remove any physically adsorbed species (ie, moisture) from the sample surface.
[0054] Test conditions included Hg fill pressure = 0.50 psia, Hg contact angle = 130°, Hg surface tension = 485 dyn / cm, Hg density = 13.53 g / mL, 30 minute evacuation time, small bore penetrometer with 5 cc balloon (solid type: 0.392 rod volume), 30 second equilibrium time, 92 point pressure gauge (75 intrusion pressure points plus 17 extrusion pressure points), and mechanical evacuation of <50 μm Hg. At about 46 psia, the crossover point from low pressure to high pressure was collected. The pressure gauge used was generated to allow for a uniform incremental distribution of pressures on a logarithmic scale from 0.5 psia to 60,000 psia, and was used to detect pore sizes from 0.003 μm to 400 μm diameter. As the pressure gradually increases from vacuum to a maximum value approaching 60,000 psia, mercury is forced into smaller and smaller pores. Table 1 below shows the resulting macropore fraction for each zirconia support calculated by dividing the total intrusion volume of 80 nm to 500 nm pores by the total intrusion volume of 3 nm to 500 nm pores.
[0055] Table 1
[0056]
[0057] The RC-100 ZrO2 carrier described in the present disclosure is purchased from Daiichi Kigenso Kagaku-Kogyo Co., Ltd. under the trade name RC-100. The MEL XZO1501 / 25 ZrO2 carrier described in the present disclosure is purchased from MEL Chemicals Inc. under the trade name or series name XZO1501 / 25. The DKKK Z3186 ZrO2 carrier described in the present disclosure is purchased from Daiichi Kigenso Kagaku-Kogyo Co., Ltd. under the trade name Z3186. The DKKK Z3101 ZrO2 carrier described in the present disclosure is purchased from Daiichi Kigenso Kagaku-Kogyo Co., Ltd. under the trade name Z3101. The NorPro SZ31164 ZrO2 carrier described in the present disclosure is a ZrO2 carrier manufactured by Saint-Gobain NorPro with the product code SZ31164.
[0058] Example 1
[0059] A metal oxide catalyst component containing gallium on a zirconium oxide support was prepared by incipient wetness impregnation. Impregnation solutions of Ga(NO3)3.xH2O and La(NO3)3.6H2O were prepared at concentrations of 1 mol / L and 0.3 mol / L, respectively, in deionized water. 10 g of a <200 mesh ZrO2 support (NORPRO SZ31164, >95% monoclinic phase measured by XRD, pore volume measured by deionized water = 0.4 mL / g) were weighed and placed in a glass vial. Afterwards, 4 mL of the Ga and La impregnation solutions were added dropwise to the support while shaking continuously. After impregnation, the catalyst was dried overnight at 85°C in an oven, then heated at incremental intervals of 3°C / min until a temperature of 550°C was reached and maintained at this temperature for 4 hours. After calcination, the catalyst was re-screened to <200 mesh (75 μm) to remove larger agglomerated particles.
[0060] Mixed catalysts were prepared by mixing 8 grams of the above metal oxide catalyst components with 1.808 grams of uncalcined SAPO-34 (<200 mesh size (75 μm)) using a mortar and pestle for 10 minutes. Separately, pseudo-boehmite (AlOOH) (manufactured by Sasol Limited, trade name Catapal D) was peptized in water with a [HNO3] / [Al] ratio of 0.05 and a total solid content of 35% by weight using HNO3 (65% by weight H2O solution). The peptized pseudo-boehmite mixture was added to the dry mixed powder, with the target being a pseudo-boehmite concentration of 24.6% by weight based on total solids. The paste was then mixed using a mortar and pestle for at least 10 minutes until a paste that could be extruded was obtained. The paste was transferred to a ceramic dish and dried overnight at 85°C. The dried precursor was heated in a static muffle furnace at an incremental interval of 2°C / min until a temperature of 600°C was reached, and then kept at this temperature for 4 hours. After calcination, the mixed catalyst was crushed and sieved into 40 mesh to 80 mesh for testing.
[0061] Example 2
[0062] A metal oxide catalyst component containing gallium on a zirconium oxide support was prepared by incipient wetness impregnation. Impregnation solutions of Ga(NO3)3.xH2O and La(NO3)3.6H2O were prepared at concentrations of 0.72 mol / L and 0.22 mol / L, respectively, in deionized water. 10 grams of a ZrO2 support (DKKK Z3186, >94% monoclinic phase measured by XRD, pore volume = 0.55 mL / g measured by deionized water) were weighed and placed in a glass vial. Afterwards, 5.5 mL of the Ga and La impregnation solutions were added dropwise to the support while continuously shaking. After impregnation, the catalyst was dried overnight in an oven at 85°C, then heated at incremental intervals of 3°C / min until a temperature of 550°C was reached, and then maintained at this temperature for 4 hours. After calcination, the catalyst was sieved to <200 mesh (75 μm) to remove larger agglomerated particles.
[0063] Mixed catalysts were prepared by mixing 8 grams of the above metal oxide catalyst components with 1.808 grams of uncalcined SAPO-34 (<200 mesh size (75 μm)) using a mortar and pestle for 10 minutes. Separately, pseudo-boehmite (AlOOH) (manufactured by Sasol Limited, trade name Catapal D) was peptized in water with a [HNO3] / [Al] ratio of 0.05 and a total solid content of 35% by weight using HNO3 (65% by weight H2O solution). The peptized pseudo-boehmite mixture was added to the dry mixed powder, with the target being a pseudo-boehmite concentration of 24.6% by weight based on total solids. The paste was then mixed using a mortar and pestle for at least 10 minutes until a paste that could be extruded was obtained. The paste was transferred to a ceramic dish and dried overnight at 85°C. The dried precursor was heated in a static muffle furnace at an incremental interval of 2°C / min until a temperature of 600°C was reached, and then kept at this temperature for 4 hours. After calcination, the mixed catalyst was crushed and sieved into 40 mesh to 80 mesh for testing.
[0064] Example 3
[0065] A metal oxide catalyst component containing gallium on a zirconia support was prepared by incipient wetness impregnation. Impregnation solutions of Ga(NO3)3.xH2O and La(NO3)3.6H2O were prepared at concentrations of 0.8 mol / L and 0.24 mol / L, respectively, in deionized water. 10 grams of ZrO2 support (XZO1501 / 25MEL Chemicals, 73% monoclinic phase measured by XRD, pore volume measured by deionized water = 0.5 mL / g) were weighed and placed in a glass vial. Afterwards, 5 mL of Ga and La impregnation solutions were added dropwise to the support while shaking continuously. After impregnation, the catalyst was dried overnight in an oven at 85°C, then heated at incremental intervals of 3°C / min until 550°C was reached, and then maintained at this temperature for 4 hours. After calcination, the catalyst was sieved to <200 mesh (75 μm) to remove larger agglomerated particles.
[0066] Mixed catalysts were prepared by mixing 8 grams of the above metal oxide catalyst components with 1.808 grams of uncalcined SAPO-34 (<200 mesh size (75 μm)) using a mortar and pestle for 10 minutes. Separately, pseudo-boehmite (AlOOH) (manufactured by Sasol Limited, trade name Catapal D) was peptized in water with a [HNO3] / [Al] ratio of 0.05 and a total solid content of 35% by weight using HNO3 (65% by weight H2O solution). The peptized pseudo-boehmite mixture was added to the dry mixed powder, with the target being a pseudo-boehmite concentration of 24.6% by weight based on total solids. The paste was then mixed using a mortar and pestle for at least 10 minutes until a paste that could be extruded was obtained. The paste was transferred to a ceramic dish and dried overnight at 85°C. The dried precursor was heated in a static muffle furnace at an incremental interval of 2°C / min until a temperature of 600°C was reached, and then kept at this temperature for 4 hours. After calcination, the mixed catalyst was crushed and sieved into 40 mesh to 80 mesh for testing.
[0067] Example 4
[0068] According to Example 2, the metal oxide catalyst component was prepared.
[0069] Mixed catalyst was prepared by mixing 4 grams of the above metal oxide catalyst components with 1 gram of uncalcined SAPO-34 (<200 mesh size (75 μm)) for 2 minutes using a mortar and pestle. Separately, 15 mL of 20 wt % zirconium acetate solution (Daiichi Kigenso Kagaku-Kogyo Co., Ltd., trade name Zircosol ZA-20) was partially neutralized by slowly adding 20 wt % ammonium zirconium carbonate (AZC) solution (Daiichi Kigenso Kagaku-Kogyo Co., Ltd., trade name Zircosol AC-20) under stirring at about 50°C until a pH of 5-6 was obtained (adding a total of 1.8 mL AZC solution). The binder solution containing Zr was added to the dry mixed powder, with the goal being a final ZrO based on total solids The binder concentration was 20 wt %. The paste was subsequently mixed using a mortar and pestle for at least 15 minutes, until a paste that could be extruded was obtained. The paste was transferred to a ceramic dish and dried at 85°C overnight. The dried precursor was heated in a static muffle furnace at 2°C / min increments up to a temperature of 600°C and then kept at that temperature for 4 hours. After calcination, the mixed catalyst was crushed and sieved into 40 to 80 mesh for testing.
[0070] Comparative Example 1
[0071] A metal oxide catalyst component containing gallium on a zirconia support was prepared by incipient wetness impregnation. Impregnation solutions of Ga(NO3)3.xH2O and La(NO3)3.6H2O were prepared at concentrations of 0.57 mol / L and 0.17 mol / L, respectively, in deionized water. 10 grams of ZrO2 support (RC-100, >94% monoclinic phase measured by XRD, pore volume measured by deionized water = 0.7 mL / g) were weighed and placed in a glass vial. Afterwards, 7 mL of Ga and La impregnation solutions were added dropwise to the support while shaking continuously. After impregnation, the catalyst was dried overnight in an oven at 85°C, then heated at incremental intervals of 3°C / min until a temperature of 550°C was reached, and then maintained at this temperature for 4 hours. After calcination, the catalyst was sieved to <200 mesh (75 μm) to remove larger agglomerated particles.
[0072] Mixed catalysts were prepared by mixing 8 grams of the above metal oxide catalyst components with 1.808 grams of uncalcined SAPO-34 (<200 mesh size (75 μm)) using a mortar and pestle for 10 minutes. Separately, pseudo-boehmite (AlOOH) (manufactured by Sasol Limited, trade name Catapal D) was peptized in water with a [HNO3] / [Al] ratio of 0.05 and a total solid content of 35% by weight using HNO3 (65% by weight H2O solution). The peptized pseudo-boehmite mixture was added to the dry mixed powder, with the target being a pseudo-boehmite concentration of 24.6% by weight based on total solids. The paste was then mixed using a mortar and pestle for at least 10 minutes until a paste that could be extruded was obtained. The paste was transferred to a ceramic dish and dried overnight at 85°C. The dried precursor was heated in a static muffle furnace at an incremental interval of 2°C / min until a temperature of 600°C was reached, and then kept at this temperature for 4 hours. After calcination, the mixed catalyst was crushed and sieved into 40 mesh to 80 mesh for testing.
[0073] Comparative Example 2
[0074] A metal oxide catalyst component containing gallium on a zirconium oxide support was prepared by incipient wetness impregnation. An impregnation solution of Ga(NO3)3.xH2O and La(NO3)3.6H2O with concentrations of 0.59 mol / L and 0.18 mol / L, respectively, in deionized water was prepared. 10 g of a ZrO2 support (DKKK Z3101, BET surface area = 80 m 2 / g, pore volume measured by deionized water = 0.68 mL / g) and placed in a glass vial. Afterwards, 6.8 mL of Ga and La impregnation solution was added dropwise to the support while shaking continuously. After impregnation, the catalyst was dried overnight in an oven at 85 ° C, then heated at an incremental interval of 3 ° C / min until a temperature of 550 ° C was reached, and then maintained at this temperature for 4 hours. After calcination, the catalyst was sieved to <200 mesh (75 μm) to remove larger agglomerated particles.
[0075] Mixed catalysts were prepared by mixing 8 grams of the above metal oxide catalyst components with 1.808 grams of uncalcined SAPO-34 (<200 mesh size (75 μm)) using a mortar and pestle for 10 minutes. Separately, pseudo-boehmite (AlOOH) (manufactured by Sasol Limited, trade name Catapal D) was peptized in water with a [HNO3] / [Al] ratio of 0.05 and a total solid content of 35% by weight using HNO3 (65% by weight H2O solution). The peptized pseudo-boehmite mixture was added to the dry mixed powder, with the target being a pseudo-boehmite concentration of 24.6% by weight based on total solids. The paste was then mixed using a mortar and pestle for at least 10 minutes until a paste that could be extruded was obtained. The paste was transferred to a ceramic dish and dried overnight at 85°C. The dried precursor was heated in a static muffle furnace at an incremental interval of 2°C / min until a temperature of 600°C was reached, and then kept at this temperature for 4 hours. After calcination, the mixed catalyst was crushed and sieved into 40 mesh to 80 mesh for testing.
[0076] Comparative Example 3
[0077] According to Comparative Example 1, a metal oxide catalyst component was prepared.
[0078] Mixed catalyst was prepared by mixing 4 grams of the above metal oxide catalyst components with 1 gram of uncalcined SAPO-34 (<200 mesh size (75 μm)) for 2 minutes using a mortar and pestle. Separately, 15 mL of 20 wt % zirconium acetate solution (Daiichi Kigenso Kagaku-Kogyo Co., Ltd., trade name Zircosol ZA-20) was partially neutralized by slowly adding 20 wt % ammonium zirconium carbonate (AZC) solution (Daiichi Kigenso Kagaku-Kogyo Co., Ltd., trade name Zircosol AC-20) under stirring at about 50°C until a pH of 5-6 was obtained (adding a total of 1.8 mL AZC solution). The binder solution containing Zr was added to the dry mixed powder, with the goal being a final ZrO based on total solids The binder concentration was 20 wt %. The paste was subsequently mixed using a mortar and pestle for at least 15 minutes, until a paste that could be extruded was obtained. The paste was transferred to a ceramic dish and dried at 85°C overnight. The dried precursor was heated in a static muffle furnace at 2°C / min increments until a temperature of 600°C was reached and then maintained at that temperature for 4 hours. After calcination, the mixed catalyst was crushed and sieved into 40 to 80 mesh for testing.
[0079] Catalytic performance data
[0080] The mixed catalyst was tested in a stainless steel fixed bed reactor system (7.7 mm inner diameter) under the following conditions: 420°C, H2 / CO=3, pressure=40 bar, WHSV=1.54 hr -1 .
[0081] Before contacting with the synthesis gas, the catalyst was heated to reaction temperature and pressure under nitrogen (N2). The reactor effluent composition was obtained by gas chromatography, and the conversion and carbon-based selectivity were calculated using the following equations:
[0082] X CO (%) = [(η CO, in – η CO, out ) / η CO, in ] · 100 (1)
[0083] S j (%) = [α j · η j, out / (η CO, in – η CO, out )] · 100 (2)
[0084] Where X CO Defined as CO conversion (%), η CO,in is defined as the molar inlet flow rate of CO (μmol / s), η CO,out is the molar outlet flow rate of CO (μmol / s), S j is defined as the carbonyl selectivity (%) for product j, α j is the number of carbon atoms in product j, and n j,out is the molar outlet flow rate of product j (μmol / s).
[0085] The results of the catalytic tests are shown in Table 2 below. The reported conversion values are the average conversion levels between 50 and 150 hours of on-stream time (TOS). The normalized deactivation rate a was calculated by fitting the data between 24 and 150 hours to a logarithmic decay: X / X0=a+k*ln(TOS(h)).
[0086] Table 2
[0087]
[0088] As can be observed in Table 2, with a macropore fraction (Φ 大Compared with the bifunctional catalyst preparations of metal oxide catalysts (Comparative Examples 1-3), based on the Φ of less than 0.3 大 The bifunctional catalyst formulations of metal oxide catalysts (Examples 1-4) showed higher conversions and lower deactivation rates k. This behavior was generally observed regardless of the polymorph of ZrO2 (Example 4) or the nature of the binder (Comparative Examples 1 and 3).
[0089] The present disclosure includes one or more non-limiting aspects. The first aspect includes a method for preparing C2 to C4 hydrocarbons, the method comprising: introducing a feed stream comprising hydrogen and a carbon-containing gas selected from the group consisting of carbon monoxide, carbon dioxide, and mixtures thereof into a reaction zone of a reactor; and converting the feed stream into a product stream comprising C2 to C4 hydrocarbons in the reaction zone in the presence of a formed mixed catalyst, the formed mixed catalyst comprising: a metal oxide catalyst component, the metal oxide catalyst component comprising gallium oxide and zirconium oxide, wherein the zirconium oxide has a macropore fraction of less than 0.3; a microporous catalyst component, the microporous catalyst component being a molecular sieve having an 8-membered ring (MR) pore opening; and a binder, the binder comprising alumina, zirconium oxide, or a mixture thereof.
[0090] A second aspect includes a method for preparing a formed hybrid catalyst, the method comprising: mixing a metal oxide catalyst component and a microporous catalyst component, wherein: the metal oxide catalyst component comprises gallium oxide and zirconium oxide, wherein the zirconium oxide has a macropore fraction of less than 0.3, and the microporous catalyst component comprises a molecular sieve having an 8-membered ring (MR) pore opening; adding a binder to the metal oxide catalyst component and the microporous catalyst component to form a paste, wherein the binder is a colloidal solution, suspension or gel of a binder precursor comprising an oxide or hydroxide of aluminum, an oxide or hydroxide of zirconium, or a mixture thereof; and extruding the paste to produce the formed hybrid catalyst.
[0091] A third aspect includes any of the above aspects, wherein the paste is calcined after extrusion.
[0092] A fourth aspect includes any of the above aspects, wherein the zirconium oxide has a macropore fraction of less than 0.25.
[0093] A fifth aspect includes any of the above aspects, wherein the zirconium oxide has a macropore fraction of less than 0.20.
[0094] A sixth aspect includes any of the above aspects, wherein the metal oxide catalyst component further comprises nickel, palladium, or platinum.
[0095] A seventh aspect includes any of the above aspects, wherein the formed mixed catalyst has a particle size of 0.5 mm to 6 mm.
[0096] An eighth aspect includes any of the above aspects, wherein the formed hybrid catalyst has a particle size of less than 3.0 mm.
[0097] A ninth aspect includes any of the above aspects, wherein the metal oxide catalyst component comprises 0.1 wt % to 10 wt % gallium.
[0098] A tenth aspect includes any of the above aspects, wherein the microporous catalyst component comprises SAPO-34.
[0099] An eleventh aspect includes any of the above aspects, wherein the microporous catalyst component comprises uncalcined SAPO-34.
[0100] A twelfth aspect includes any of the above aspects, wherein the binder comprises pure alumina.
[0101] A thirteenth aspect includes any of the above aspects, wherein the binder comprises pure zirconium oxide.
[0102] A fourteenth aspect includes any of the above aspects, wherein the metal oxide catalyst component comprises 40.0 wt % to 85.0 wt % of the formed hybrid catalyst.
[0103] A fifteenth aspect includes any of the above aspects, wherein the C2-C4 hydrocarbons primarily include C2-C4 olefins.
[0104] The subject matter of the present disclosure has been described in detail and by reference to specific embodiments. It should be understood that any detailed description of a component or feature of an embodiment does not necessarily imply that the component or feature is essential to the specific embodiment or any other embodiment. Further, it will be apparent to those skilled in the art that various modifications and changes may be made to the described embodiments without departing from the spirit and scope of the claimed subject matter.
[0105] It should be noted that one or more of the appended claims utilize the term "wherein" as a transitional expression. For purposes of defining the present technology, it should be noted that this term is introduced in the claims as an open transitional phrase that is used to introduce a recitation of a series of features of a structure and should be interpreted in a manner similar to the more commonly used open-ended term "comprising."
[0106] It should be understood that where a first component is described as "comprising" a second component, it is contemplated that in embodiments, the first component "consists of" or "consists essentially of" the second component. It should also be understood that where a first component is described as "comprising" a second component, it is contemplated that in embodiments, the first component may comprise at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95%, or even at least 99% of the second component (wherein % may be wt % or mole %).
[0107] For purposes of describing and defining the present technology, it should be noted that references herein to a variable that is a "function" of a parameter or another variable are not intended to indicate that the variable is exclusively a function of the listed parameter or variable. Rather, references herein to a variable that is a "function" of the listed parameters are intended to be open-ended such that the variable may be a function of a single parameter or multiple parameters.
[0108] It should also be noted that reference herein to "at least one" component, element, etc. should not be used to create an inference that alternative use of the article "a / an" should be limited to a single component, element, etc.
[0109] For purposes of describing and defining the present technology, it is noted that the terms "substantially" and "approximately" are used herein to represent the inherent degree of uncertainty that may be attributed to any quantitative comparison, value, measurement, or other representation. The terms "substantially" and "approximately" are also used herein to represent the degree by which a quantitative representation may vary from a stated reference without resulting in a change in the basic function of the subject matter at issue.
Claims
1. A method for preparing C2 to C4 hydrocarbons, the method comprising: introducing a feed stream comprising hydrogen and a carbon-containing gas selected from the group consisting of carbon monoxide, carbon dioxide, and mixtures thereof into a reaction zone of a reactor; as well as The feed stream is converted into a product stream comprising C2 to C4 hydrocarbons in the reaction zone in the presence of a formed mixed catalyst comprising: a metal oxide catalyst component comprising gallium oxide and zirconium oxide, wherein the zirconium oxide has a macropore fraction of less than 0.3; A microporous catalyst component, wherein the microporous catalyst component is a molecular sieve having 8-membered ring (MR) pore openings; and The binder comprises aluminum oxide, zirconium oxide or a mixture thereof.
2. A method for preparing a formed mixed catalyst, the method comprising: A mixed metal oxide catalyst component and a microporous catalyst component, wherein: The metal oxide catalyst component comprises gallium oxide and zirconium oxide, wherein the zirconium oxide has a macropore fraction of less than 0.3; and The microporous catalyst component comprises a molecular sieve having 8-membered ring (MR) pore openings; adding a binder to the metal oxide catalyst component and the microporous catalyst component to form a paste, wherein the binder is a colloidal solution, suspension or gel of a binder precursor comprising an oxide or hydroxide of aluminum, an oxide or hydroxide of zirconium, or a mixture thereof; and The paste is extruded to produce the formed mixed catalyst.
3. The method of claim 2, wherein the paste is calcined after extrusion.
4. The method according to any one of claims 1 to 3, wherein the zirconium oxide has a macropore fraction of less than 0.
25.
5. The method according to any one of claims 1 to 3, wherein the zirconium oxide has a macropore fraction of less than 0.
20.
6. The method according to any one of claims 1 to 5, wherein the metal oxide catalyst component further comprises nickel, palladium or platinum.
7. The process according to any one of claims 1 to 6, wherein the formed mixed catalyst has a particle size of 0.5 mm to 6 mm.
8. The process according to any one of claims 1 to 7, wherein the formed mixed catalyst has a particle size of less than 3.0 mm.
9. The process according to any one of claims 1 to 8, wherein the metal oxide catalyst component comprises 0.1 wt% to 10 wt% gallium.
10. The method of any one of claims 1 to 9, wherein the microporous catalyst component comprises SAPO-34.
11. The process of any one of claims 1 to 10, wherein the microporous catalyst component comprises uncalcined SAPO-34.
12. The method according to any one of claims 1 to 11, wherein the binder comprises pure alumina.
13. The method according to any one of claims 1 to 12, wherein the binder comprises pure zirconium oxide.
14. The process of any one of claims 1 to 13, wherein the metal oxide catalyst component comprises from 40.0 wt% to 85.0 wt% of the formed hybrid catalyst.
15. The method according to any one of claims 1 or 4 to 14, wherein the C2 to C4 hydrocarbons mainly include C2 to C4 olefins.